Where Are We? The Level of Risk Management in Malaysian Construction Industries - Mohd Nawi, Mohd Nasrun; Adeleke, A.Q.; Abd-Karim, Saipol Bari (International Journal of Supply Chain Management, 2020)
Over the decade, the level of risk management has always been lingering in every construction industry sectors. Therefore, this research deeply investigated the level of risk management among Kuantan Malaysian construction industries to better promote effectiveness on risk management implementation within the industry. To address this issues, this study makes use of statistical package for the social sciences (SPSS) approach to validate construction risk management (CRM) as a construct from registered Grade-7 contractors operating in Malaysia point of view. With a cross-sectional survey and proportionate stratified random sampling techniques, data were gathered from 87 G-7 contractors through a structured questionnaire. Methodologically, this research perhaps might be the first to determine the level of risk management where Kuantan Malaysian construction industries belong to. Using the five-point Likert scale categories (very low, low, medium, high and very high) of risk management from previous studies, statistical analysis affirmed that the overall level of risk management among Kuantan Malaysian construction industries is at the high level.